ANALYSIS OF THE STABILITY OF THE T1 SECTION OF THE OUTLET WATER TUNNEL BASED ON CONVERGENT MEASUREMENTS OF THE NANJUNG WATER TUNNEL - Llang Mayo, Keithcar
The Nanjung Water Tunnel is a twin tunnels that is used to drain the water of the Citarum River in Curug Jompong, Kecamatan Margaasih, Kabupaten Bandung. In the construction of the Nanjung Water Tunnel development project, the stability of the tunnel is an important thing to note. At the time of excavation there will be a voltage redistribution until a new equilibrium condition is reached. In the process of achieving this equilibrium, there will be a displacement event in the rock mass of opening hole besides the presence of a large and continuous displacement rate which, if not driven, could potentially cause tunnel collapse or collapse. In this final project, we will analyze the stability of the tunnel by measuring the relative displacement between the two points on the excavation limit, or called the convergent measurement by using the convergencemeter tool. The stability analysis criteria to be used are based on the concept of critical strain Sakurai (1983) and rate of displacement UG Geotech PT Freeport Indonesia (2000). From the analysis of stability criteria, the Nanjung T1 Water Tunnel can be said to be stable or not have a significant buffer problem if the large strain is smaller than 1.25%. While based on the criteria for rate of displacement UG Geotech PT Freeport Indonesia (2000) are divided into 5 categories, namely negligible, moderate, severe, very severe, dan extremely severe. The displacement rate can be said to be stable or negligible if the displacement rate is smaller than 1 mm/day, moderate for the displacement rate of 1-2 mm/day, severe for the displacement rate of 2-3 mm/day, very severe for the displacement rate of 3-5 mm/day, and extremely severe for a displacement rate of more than 5 mm / day. The results of the analysis showed instability in the STA 0+120 Water Tunnel T1 Nanjung so that the factors that were expected to influence the stability of the STA must be analyzed.